Potensi Bakteri Asam Laktat Sebagai Penghasil Eksopolisakarida Dari Dekke Na Niura - Nasution, Anggy Yohanna; Rasyidah, Rasyidah; Mayasari, Ulfayani (Universitas Al Azhar Indonesia, 2022)
Dekke Na Niura is a typical traditional food of Batak Toba tribe which is made from fermented carp. Dekke Na Niura can act as a source of probiotics because it contains good microorganisms, namely Lactic Acid Bacteria (LAB). Several types of LAB are known synthesize exopolysaccharides (EPS), which are polysaccharide polymers considered important for health. Therefore researchers want to know whether dekke na niura can act as functional food evidenced by the presence of LAB and its potential to produce EPS. The presence of bacterial isolate on dekke na niura was detected by dilution series-pour plate method on MRSA (deMan Rogosa and Sharpe Agar) medium, then confirmed as LAB by morphological and biochemical characterization. The isolates believed to be LAB were then tested for their potential to produce EPS. The results showed that in dekke na niura, LAB isolates were found by UB1, UB2 and UB3 and then all of them identified as Lactobacillus. The three isolates showed the potential for EPS production with a weight ranging from 2490-3490 mg/L. This weight is known to be greater than the weight of EPS produced by commercial LAB isolates.Keywords – Carp, Dekke Na Niura, Lactic Acid Bacteria, Exopolisaccharides